Implementasi Program Literasi untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar: Implementing a Literacy Program to Increase the Learning Motivation of Elementary School Students - Raoda Raoda; Ince Prabu Setiawan; Abdul Wahid (Madrasah Tsanawiyah DDI Cilellang, 2023)
The lack of awareness of elementary school students' literacy results in low student learning motivation from childhood. This study aims to analyze: (1) the implementation of the literacy program in increasing student motivation; and (2) the supporting and inhibiting factors in implementing the literacy program. This study uses a qualitative method with a phenomenological approach. The object of this research is the students of Butung II Public Elementary School, Makassar City, Indonesia. The results of the study show that the literacy program is implemented in three ways: independent quizzes, literacy classes, and Friday prayers. These various literacy programs have implications for increasing student learning motivation. This is proven by the fact that students prefer to read textbooks, start writing stories, and dare to appear to speak in front of their friends. Factors supporting this program are teaching campus students, teacher cooperation, the active role of students, and school appreciation. The inhibiting factors are the lack of support from students' parents and inadequate educational facilities. This research has implications for the need for teachers' ability to choose and sort out the right literacy program (according to students' needs and interests) to increase student motivation.